ANALISIS KETERTARIKAN PEMBELIAN PRODUK LUAR NEGERI PADA MASYARAKAT PERBATASAN INDONESIA-MALAYSIA DI DESA ENTIKONG KECAMATAN ENTIKONG - Agnes Dwini; Okianna Okianna; Jumardi Budiman (KAMPUS AKADEMIK PUBLISING, 2026)
This research was conducted in Entikong Village, Entikong District, Sanggau Regency, with the aim of analyzing the purchasing interest in foreign products among communities living in the Indonesia–Malaysia border area and identifying the influence of distance factors on their purchasing interest. Border areas have unique characteristics due to relatively easy access to goods from neighboring countries, which can influence local consumption patterns. This study employed a qualitative approach using a case study method. The informants consisted of 10 border community members who frequently purchased foreign products. Data were collected through interviews, observations, and documentation. The results showed that the border community in Entikong Village has a relatively high interest in purchasing foreign products. This interest is influenced by several factors, including the relatively lower prices of foreign products, the short and easily accessible travel distance, and the level of satisfaction with the products purchased. In addition, respondents perceived that some foreign products offer larger quantities and better value compared to similar domestic products. Therefore, price, distance, and consumer satisfaction are the main factors influencing the purchasing interest of border communities in foreign products.